Struktur dan Skala Upah sebagai Instrumen Strategis Transparansi dan Keadilan Pengupahan serta Implikasinya terhadap Kepuasan Kerja Karyawan: (Systematic Literature Review) - Jarot Marsono; Faidh Rahmani Nasr; Henry Anggoro Djohan; Muhammad Ikhwan Al Ghifari (Lembaga Pengembangan Kinerja Dosen, 2026)
Wage transparency is a strategic issue in human resource management because it is closely related to compensation fairness, employee trust, job satisfaction, and industrial relations stability. One instrument that can support proportional wage transparency is the wage structure and scale, which provides an objective basis for explaining pay differences across positions, competencies, tenure, responsibilities, and performance. This article aims to systematically examine the role of wage structure and scale as a strategic instrument for strengthening wage transparency and pay fairness, as well as its implications for employee job satisfaction. This study uses a Systematic Literature Review approach by synthesizing relevant national and international literature on wage structure, pay transparency, compensation fairness, organizational justice, and job satisfaction. The findings show that a clearly designed and consistently communicated wage structure and scale can strengthen transparency in compensation decisions, reduce ambiguity in pay determination, enhance employees’ perceptions of distributive and procedural fairness, and contribute to job satisfaction. This study implies that wage structure and scale should not only be treated as regulatory compliance, but also as a strategic human resource management instrument for building trust, preventing wage-related conflict, and supporting harmonious industrial relations.